Results of Ukrainian Adaptation of the Pediatric Symptom Checklist with Abused Children - Olena Lutsenko; Diana Shtryhol; Nataliia Mikhanovskaya (Вісник Харківського національного університету імені В.Н. Каразіна. Серія: Психологія, 2022)
The aim of the study was to adapt a very popular in the world screening questionnaire for assessment of children psychosocial functioning. Both (parent and youth) versions of Pediatric Symptom Checklist (PSC, Y-PSC) of M. S. Jellinek, J. M. Murphy et al. were validated in Ukraine so to find out their cross-cultural universality and usefulness. The total number of study participants was 532: 281 parents fulfilled PSC-Ukr and 251 children fulfilled Y-PSC-Ukr. The sample included ordinary children, ones from families with domestic abuse and small clinical sample. Clinical interview, Kinetic Family Drawings and Sentence Completion Test were used with PSC questionnaires. Methods of classical test theory, confirmatory factor analysis and ROC-analysis were used for tests validation. Adapted versions appeared reliable and valid but had unusually low cut-offs and two-factor structure (internalizing and externalizing symptoms without separate attention deficit factor). Weak economy, military actions and upbringing peculiarities can be the reasons of unusual cut-off and factor structure of adapted tests. This test will be useful for practitioners and researchers in mental health and social work areas. PSC-Uke Y-PSC-Ukr can be recommended for use with problematic populations like children from families with domestic abuse as these methods reveal forms and degrees of children’s psychosocial dysfunction through negative growth conditions.